The Partial Support of the Left Ventricular Assist Device Shifts the Systemic Cardiac Output Curve Upward in Proportion to the Effective Left Ventricular Ejection Fraction in Pressure-Volume Loop - Kakino, Takamori; Saku, Keita; Nishikawa, Takuya; Sunagawa, Kenji (Frontiers in Cardiovascular Medicine, 2020)
Left ventricular assist device (LVAD) has been saving many lives in patients with severe left ventricular (LV) failure. Recently, a minimally invasive transvascular LVAD such as Impella enables us to support unstable hemodynamics in severely ill patients. Although LVAD support increases total LV cardiac output (COTLV) at the expense of decreases in the native LV cardiac output (CONLV), the underlying mechanism determining COTLV remains unestablished. This study aims to clarify the mechanism and develop a framework to predict COTLV under known LVAD flow (COLVAD). We previously developed a generalized framework of circulatory equilibrium that consists of the integrated CO curve and the VR surface as common functions of PRA and left atrial pressure (PLA). The intersection between the integrated CO curve and the VR surface defines circulatory equilibrium. Incorporating LVAD into this framework indicated that LVAD increases afterload, which in turn decreases CONLV. The total LV cardiac output (COTLV) under LVAD support becomes COTLV = CONLV+EFe•COLVAD, where EFe is effective ejection fraction, i.e., Ees/(Ees+Ea). Ees and Ea represent LV end-systolic elastance (Ees) and effective arterial elastance (Ea), respectively. In other words, LVAD shifts the total LV cardiac output curve upward by EFe•COLVAD. In contrast, LVAD does not change the VR surface or the right ventricular CO curve. In 6 anesthetized dogs, we created LV failure by the coronary ligation of the left anterior descending artery and inserted LVAD by withdrawing blood from LV and pumping out to the femoral artery. We determined the parameters of the CO curve with a volume-change technique. We then changed the COLVAD stepwise from 0 to 70-100 ml/kg/min and predicted hemodynamics by using the proposed circulatory equilibrium. Predicted COTLV, PRA, and PLA for each step correlated well with those measured (SEE; 2.8 ml/kg/min 0.17 mmHg, and 0.65 mmHg, respectively, r2; 0.993, 0.993, and 0.965, respectively). The proposed framework quantitatively predicted the upward-shift of the total CO curve resulting from the synergistic effect of LV systolic function and LVAD support. The proposed framework can contribute to the safe management of patients with LVAD.